PENDEKATAN DEEP LEARNING TERHADAP PEMBELAJARAN SISWA DAN SISWI PAUD MUTIARA DI SKB KOTA CILEGON - Nujma Kamila Fitri; Ahmad Rizaldi; Rahmat Hidayatulloh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The deep learning approach in the learning process of Mutiara Early Childhood Education students at SKB Kota Cilegon focuses on cognitive development, fine motor skills, and active participation. The research method used is descriptive qualitative, involving students aged 4-6 years through three learning sessions with the themes “Air vehicles” and “Colestical Objects”. Data were collected through observations, student worksheet, post-learning evaluations, and documentation. Learning activities included writing exercises, paper folding projects (making airplanes and helicopter), and making rainbows from colored paper. The result showrd that deep learning approach had a positive impact on students cognitive abilities, with students being able to answer questions correctly during the evaluation. Students became more actively involved in learning activities, showed increased curiosity, and experienced better fine motor development through project-based activities. Visual media in the form of worksheets containing colored images proved effective in helping students acquire information quickly. However, implementation challenges remain, including limited acces to teacher training, inadequate infrastructure,and a curriculum that is not aligned with deep learning principles. The deep learning approach has proven effective in improving the quality of early childhood learning through active, collaborative, and meaningful learning experiences, although its optimization requires the support of teacher competency, an appropriate curriculum, and adequate facilities.